Socio-economic indicators of nuclear energy investments: A study on countries - Yüksel, Serhat; Dinçer, Hasan; Uluer, Gülsüm Sena (Emerald Group Publishing Ltd., 2023)
With the increase in population, the energy needs of countries are also increasing. These countries have difficulties in meeting these increasing needs. Countries that cannot meet this need have to import energy from abroad. This situation adversely affects the current account balance of countries. Nuclear energy investments allow countries to obtain their own energy, although there are some criticisms. In this framework, while some countries in the world increase their nuclear energy investments, some countries do not have any nuclear power plants (NPP). There are 32 such countries where nuclear energy projects are running till date. Therefore, it is very important to determine the socio-economic variables of countries that have nuclear energy investments. In this context, a detailed literature analysis will be made first to determine socio-economic criteria. Then, the importance weights of these factors will be calculated using the Decision Making Trial and Evaluation Laboratory (DEMATEL) method. The profiles of the countries that make nuclear energy investments demonstrate that education level is the most essential socio-economic factor for the improvement of nuclear energy investments. Also, income inequality is another important variable in this regard. However, consumption behaviour and saving behaviour have the lowest weights.
Keywords: Dematel; Energy Dependence; Energy Investment; Income Inequality; Nuclear Energy; Socio-Economic Indicators